Mentoring Youth in Creative Entrepreneurship to Enhance Community Independence - Khattak, Waseem Ahmed (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
This community service project was initiated in response to the growing need to empower rural youth through creative entrepreneurship as a means of promoting community independence and economic resilience. The program aimed to mentor young individuals in developing creative, innovative, and sustainable business ventures using the Service Learning (SL) approach. Conducted over six months in Desa Sukamaju with 30 youth participants, the project combined mentoring sessions, workshops, and practical business development activities. Data were collected through observation, interviews, and pre- and post-assessments, then analyzed using both qualitative thematic analysis and quantitative correlation tests. The findings revealed significant improvements in participants’ entrepreneurial literacy, creativity, and self-efficacy, strongly correlated with the intensity of mentoring activities. The project also strengthened community solidarity and stimulated the local creative economy. In conclusion, SL-based mentoring proved to be an effective and sustainable model for youth empowerment, bridging academic engagement and community development.